The impact of family socioeconomic status on adolescent mental and physical health: the mediating role of parental involvement in youth sports - Yang, Wenli; Xiang, Zubing; Hu, Hong; Zheng, Haoyuan; Zhao, Xin (Frontiers in Public Health, 2025)
IntroductionThe physical and mental health of adolescents is a crucial cornerstone for social development. Therefore, this study aimed to examine whether family socioeconomic status made a difference in Chinese teenage mental and physical health and to disentangle the mediating role of parental involvement in youth sports in the process in which family socioeconomic status influenced adolescent health.MethodsA quantitative analysis used a sample of approximately 11,000 adolescents from Chinese middle schools. The research employed structural equation modelling (SEM) to explore the relationships among family socioeconomic status, parental involvement in youth sports, and adolescent mental and physical health.ResultsThe findings indicated that both family socioeconomic status and parental involvement in youth sports significantly positively predict levels of adolescents’ physical health and mental health. Further analysis revealed that parental involvement in youth sports mediated the relationship between family socioeconomic status and adolescent health.DiscussionIt is evident that parental involvement in youth sports plays a crucial role in adolescent mental and physical health. Regardless of family socioeconomic status, parents should actively engage in sports activities with their children, which is not only an important way to promote adolescents’ health but also a manifestation of realizing health equity.